Integrating AI-Assisted Speaking Platforms to Enhance English Speaking Skills among Polytechnic Students - Yeni Latipah; Dini Hadiani; Fajrin Mubarokah Parhani; Ahshonat Khoerunnisa (Research Collaboration Community (Rescollacom), 2026)
English speaking skills are essential for polytechnic students to meet the communicative demands of an increasingly globalized workforce. However, many students face difficulties in developing oral proficiency due to limited speaking opportunities, low confidence, and anxiety in classroom settings. This study investigates the integration of an AI-assisted speaking platform to enhance English speaking skills among polytechnic students. Employing a descriptive qualitative research design, the study was conducted over four instructional meetings in an English for Technique course and involved 60 students from two classes. Data were collected through classroom observations, questionnaires, and analysis of students’ speaking practice supported by feedback provided through the AI-assisted speaking platform. The findings indicate that the platform supported the development of key speaking components, particularly pronunciation, fluency, and grammatical awareness, by enabling repeated and self-paced practice. In addition, the use of AI-assisted speaking contributed to increased speaking confidence and learner autonomy through immediate and intelligible feedback. Despite these positive outcomes, several challenges were identified, including technical constraints, limitations in interactional naturalness, and the need for pedagogical scaffolding. The study concludes that AI-assisted speaking platforms can serve as effective supplementary tools for enhancing English speaking instruction in polytechnic education when thoughtfully integrated into classroom practice.